2010
DOI: 10.1080/19338244.2010.486426
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Hazards of Waste Disposal Patterns—A Multimethod Study in an Unrecognized Bedouin Village in the Negev Area of Israel

Abstract: The Bedouin of the Negev region of Israel are a formerly nomadic, indigenous, ethnic minority, of which 40% currently live in unrecognized villages without organized, solid waste disposal. This study, using both quantitative and qualitative methods, explored the transition from traditional rubbish production and disposal to current uses, the current composition of rubbish, methods of waste disposal, and the extent of exposure to waste-related environmental hazards in the village of Um Batim. The modern, consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Since the unrecognized villages lack official government recognition, they have no formal system of local government and pay no taxes. They also do not receive municipal funds, and lack basic municipal infrastructure like water, sewer access and organized waste disposal (Meallem, Garb and Cwikel 2010). Moreover, any domestic structures that are formally classified as illegal are under on-going risk of being torn down, so they tend to be temporary, composed of light substances such as fabric, tin or wood.…”
Section: Placing the Study In Contextthe Negev Bedouin And The Life O...mentioning
confidence: 99%
“…Since the unrecognized villages lack official government recognition, they have no formal system of local government and pay no taxes. They also do not receive municipal funds, and lack basic municipal infrastructure like water, sewer access and organized waste disposal (Meallem, Garb and Cwikel 2010). Moreover, any domestic structures that are formally classified as illegal are under on-going risk of being torn down, so they tend to be temporary, composed of light substances such as fabric, tin or wood.…”
Section: Placing the Study In Contextthe Negev Bedouin And The Life O...mentioning
confidence: 99%
“…Studies of Bedouin children reflect a similar spatial distinction in gender roles, with boys ranging farther afield, undertaking tasks such as herding sheep, while girls stay close to home with their mothers. One consequence of this is that women and children in the unrecognized Bedouin villages have higher rates of exposure to environmental toxins, like the smoke from backyard trash burning, than the men and older boys, whose work takes them farther from their village's immediate proximity (Meallem, Garb and Cwikel 2010).…”
Section: Nature Connectedness and Culturementioning
confidence: 99%
“…For hundreds of years, the Negev Bedouins maintained their natural environment, in part because nearly all of the waste they generated was organic and easily biodegradable. Today, however, Bedouin society has incorporated many modern, inorganic materials into daily life, and the contents of the waste it generates have changed accordingly (Meallem et al 2010). This change, combined with the fact that the unrecognized villages do not have organized waste removal services, means that the population of these villages is subject to the constant environmental and health hazards associated with pollution.…”
Section: Feelings Of Concern and Responsibilitymentioning
confidence: 99%
“…As a result, the residents must dispose of their waste themselves. Studies of settlements with similar waste-disposal issues have shown that the lack of the means and knowledge for proper disposal, together with the combined inaction of the government and the community in addressing this lack, can lead to environmental and health problems like foul smells, the agglomeration and reproduction of harmful insects and bacteria, and the outbreak of infectious diseases (Ismail et al 2017) and dumping of waste in streams and streambeds (Meallem et al 2010;Authors, 2014). It is worth noting that practices like incineration or leaving waste to biodegrade worked reasonably well in the days when Bedouin communities were smaller, nomadic, and generated waste that was almost entirely organic.…”
Section: The Bedouins and Their Relationship With Placementioning
confidence: 99%
“…This balance, however, relied at least in part on the fact that their population was small, and nearly all of the waste they generated was organic and easily biodegradable. Today, Bedouin society has incorporated many modern, inorganic materials into daily life, and the contents of the waste it generates have changed accordingly (Meallem et al 2010). The adoption of a sedentary life, and of many Western products and practices (e.g.…”
Section: B) From Resignation To Responsibilitythe Benefits Of Combinimentioning
confidence: 99%